Integrasi Nilai Ekologis Al-Qur’an dalam Konsep Ekonomi Hijau Islam untuk Pembangunan Berkelanjutan - Hanif, Khairul; Muhammad Adnan Azzaki (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2025)
The concept of Islamic Green Economy integrates Islamic dluprinciples into a sustainable development framework, emphasizing the responsibility of humans as God's vicegerents on earth to maintain ecological balance and environmental sustainability. This study uses a qualitative-descriptive approach with a literature study method, where data are obtained from verses of the Qur'an, classical and contemporary interpretations, and scientific articles relevant to the issue of sustainability in Islam. The results of the study indicate that environmental ethics in the Qur'an such as the prohibition of destruction (fasad) in QS. Al-A'raf [7]: 56, the principle of balance (mizan) in QS. Ar-Rahman [55]: 7–8, and the trust towards nature in QS. Al-Ahzab [33]: 72 serve as the theological foundation for sustainable development in Islam. This study makes an academic contribution by showing how Islamic ecological values ​​can be integrated into a green economy framework, while providing a moral and ethical basis for sustainable development policies in Muslim countries.